Taxonomical remarks on Promenaea microptera (Orchidaceae: Epidendroideae): the rediscovery of a poorly known micro-endemic orchid from the Brazilian Atlantic Forest - Fajardo V. A. Barberena, Felipe; Rodrigues Gastin, Jorge; de Camargo Smidt, Eric (Phytotaxa, 2022)
N/A